Experimental thermal hazard investigation on carbonate electrolytes using a cone calorimeter. (June 2021) - Huang, Que; Lu, Song; Liu, Xiaozhao; Zheng, Kaihui; Xu, Dengji; Liu, Changcheng
Abstract: During the thermal runaway (TR) processing of lithium-ion batteries (LIBs), electrolyte would release most of the heat as the main component. Thus, study on the fire risk of electrolyte is conductive to quantitatively evaluate the safety of LIBs. In this work, the combustion characteristics of three kinds of carbonate mixture electrolytes and the composition of residue were investigated. The significant parameters from the cone calorimeter tests reflecting the thermal hazards such as heat release rate (HRR), mass loss rate (MLR) and open cup flash point were measured. The HRR curves at the radiant power of 15 and 25 kW/m 2 were more gradual than those at 35 kW/m 2 which had one or two apparent peaks. The addition of diethyl carbonate (DEC) increased the HRRs significantly. The applicability of thermal chemistry (TC) theory used to calculate HRR in previous works was studied. The results of TC technique had a disparity with those from the cone calorimeter called oxygen consumption (OC) calorimetry especially for the electrolyte containing DEC, which was proved by thermogravimetry-Fourier transform infrared spectroscopy (TG-FTIR) experimental results, while it is different from the conclusion reported in previous study. The constituent of carbonate electrolytes residue was analyzed by the X-ray Fluorescence (XRF). Element fluorine (F) accounted for over 90% of the residue. The open cup flash point and ignition temperature were determined by the open cup flash point apparatus. The results showed that the fire point was very close to the open cup flash point, and the difference was within 0.1 K. Graphical abstract: The reason why heat release rate (HRR) of electrolyte blends containing diethyl carbonate (DEC) calculated by thermal chemistry (TC) theory existing errors when comparing with that from oxygen consumption (OC) calorimetry is that DEC promoted CO2 production through internal chemical reactions, while TC method regards all the CO2 production are from combustion during the heating processing. Thus, OC calorimetry is more appropriate than TC theory when calculating HRR of electrolyte mixtures containing DEC. The illustration is as presented in Figure GA. Figure GA. The mechanism of CO2 production influence on errors between TC theory and OC calorimetry. Image 1 Highlights: The addition of DEC and EMC decreased the open cup flash points significantly. The HRR curves of the three mixtures appeared extra higher peaks under higher radiation power. The great disparity of CO2  production of the three samples leaded to the errors between TC theory and OC calorimetry.